Leadership and Management : Global Warming Impact on Policing: An analysis of security preparedness - Mayar, Ring (IJRDO-Journal of Applied Science, 2017)
In recent years a range of provocative thinkers have gathered in Canberra to debate the impact of climate change on law enforcement beyond the 21st century. For nearly a century, the police strategies have remained unchallenged. Police or security agencies interchangeably have engaged in parallel strategies to prepare for the emerging issues and enabled them to carry out their duties responsibly. Nowadays, the climate change concern remains as the most futuristic obstacle that will pose serious problem to policing. The law enforcement agencies previously have always enjoyed the privilege to acquire limitless information, share ideas and experiences worldwide, to have adequate education and training opportunities, and so developing a better understanding of police future conflict dimensions. However, the flip side of the coin is that the entire world is quickly confronted with climate change threats (Abbott, 2008), emerging security issues from various social, environmental and political influences which did not previously fall under conventional notions of “defence”. Within the next two decades, the demands for policing and expectation will be far greater and more complex. Moreover, police leadership will be hit with high demands for multi skilled forces and resources constraints. In addition, operational ambiguity will contradict leadership strategic planning to achieve civility, order and security. The influx of climate change refugees from neighbouring islands may contribute to the causes of violence and unruly behaviour. In this situation, modern police skills, resources to high expectation to serve the community should not be overlooked. Therefore, it is vital for the future leadership in policing to identify those key trends that will demand law enforcement diligence in achieving maximum expenditure of efforts and resources.